2018
DOI: 10.1097/bpo.0000000000001115
|View full text |Cite
|
Sign up to set email alerts
|

Toe Walking: A Neurological Perspective After Referral From Pediatric Orthopaedic Surgeons

Abstract: Level III-retrospective cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…The vast majority of reasons for toe walking gait are neurological in origin [ 23 ]. These is building evidence of ITW also resulting from subtle neurological differences between toe walking and non-toe walking peers [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of reasons for toe walking gait are neurological in origin [ 23 ]. These is building evidence of ITW also resulting from subtle neurological differences between toe walking and non-toe walking peers [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the correlation with toe walking and other underlying disorders. Haynes reported that 62% of patients referred to neurology for toe walking had an underlying disorder including cerebral palsy, peripheral neuropathy, autism spectrum disorder (ASD), and hereditary spastic paraparesis 49. Leyden et al50 found a higher prevalence of prolonged toe walking in children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…An important finding was that 71% of children with asymmetric TW had an eventual diagnosis of hemiplegic CP. 3 Although no single examination measurement is diagnostic, a comprehensive examination, including the foot, spine, general gait, and ROM, and neurologic examination are important. On visual gait examination, it is important to determine whether the child can walk in a heel-toe manner when asked.…”
Section: Diagnosismentioning
confidence: 99%
“…15 When history or physical examination findings are abnormal, a consultation with a neurologist is warranted. Haynes et al 3 found in their series of children with abnormal or asymmetric ITW referred to pediatric neurology from pediatric orthopaedics, 62% were determined to have an underlying pathologic cause. If those children with autism and ADHD are excluded, the diagnosis of a pathologic cause was still 47%.…”
Section: Geneticsmentioning
confidence: 99%